Effect of thermal neutron irradiation on the electrophysical and photoelectric properties of Hg₀.₈Cd₀.₂Te crystals - Virt, I.S.; Gorbunov, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We have studied experimentally the effect of thermal neutron irradiation on the electrophysical and photoelectric parameters of Hg₁₋xCdxTe crystals. The irradiation was shown to produce both donor- and acceptor-type radiation defects. In this case the majority charge carrier mobility decreases significantly. An analysis is given of a model for radiation defect production. The photoconduction processes are explained from the standpoint of clusterization of such radiation defects.